2019
DOI: 10.2147/ott.s206861
|View full text |Cite
|
Sign up to set email alerts
|

<p>tRNA-derived fragment tRF-03357 promotes cell proliferation, migration and invasion in high-grade serous ovarian cancer</p>

Abstract: Background High-grade serous ovarian cancer (HGSOC) is one of the most common ovarian epithelial malignancies. tRNA-derived fragments (tRFs) have been identified as novel potential biomarkers and targets for cancer therapy. Nevertheless, the influence of tRFs on HGSOC remains unknown. This study aimed to identify HGSOC-associated tRFs and to investigate the function and mechanism of key tRFs in SK-OV-3 ovarian cancer cells. Methods The tRF profiles in HGSOC patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 34 publications
3
95
0
Order By: Relevance
“…tsRNAs were veri ed to be associated with numerous diseases, such as metabolic disorder, pathological stress injuries, neurodegenerative diseases, virus infection as well as cancer (9). In elds related to cancer research, expression pro le and biological function of tsRNAs were reported in chronic lymphocytic leukemia (CLL) (10,11), lung cancer (5,10,12), colorectal cancer (5, 13), breast cancer (5, 14-17), ovarian cancer (5,18,19) and prostate cancer (20,21). However, tsRNAs have not been elucidated in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…tsRNAs were veri ed to be associated with numerous diseases, such as metabolic disorder, pathological stress injuries, neurodegenerative diseases, virus infection as well as cancer (9). In elds related to cancer research, expression pro le and biological function of tsRNAs were reported in chronic lymphocytic leukemia (CLL) (10,11), lung cancer (5,10,12), colorectal cancer (5, 13), breast cancer (5, 14-17), ovarian cancer (5,18,19) and prostate cancer (20,21). However, tsRNAs have not been elucidated in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, reported that tRFs were involved in cell transcription, migration, and interaction with the MAPK and Wnt signaling pathways. Moreover, tRF-03357 was predictively targeted, due to promoting cell proliferation, migration, and invasion [55].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…For example, tsRNAs derived from tRNA(Glu), tRNA(Asp), tRNA(Gly), and tRNA(Tyr) suppress cancer cell growth and metastasis [ 16 ]. In contrast, tsRNA-26576 promotes breast cancer cell proliferation while inhibiting apoptosis [ 21 ], and tRF-03357 promotes ovarian cancer cell growth and migration [ 22 ]. In addition, tRF5-AlaCGC enhances the secretion of IL-8 in response to arsenite, via p65 activation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%